GIVE AWAY VIOLENCE, PRESERVE LIFE: CONTEMPORARY CALL OF THE SRAMANA RELIGIONS - Sekhar, Vincent (Journal of Dharma, 2000)
Religion gives meaning to society. It operates from ultimate perspectives, in terms of end or goal of life. It does not provide merely an abstract creed as a set of beliefs, but offers at the level of behaviour certain ethical principles through which the believing community seeks to reach the proposed goals. It is the task of religion to orient the whole of life, the common good of humanity, etc.